(untitled) (Albayan Scientific Journal, 2023)
This study is concerned with the use of cold formed steel channel sections as purlins in metal roofed buildings. This section type represents the mono-symmetric case. Uniformly distributed loads both in the downward as well as the upward direction will be considered. In all cases beams will be considered as simply supported. Cold-formed channel sections are widely used as cross-section of structural members, such as purlins to support roof sheeting. Connecting of roof sheeting to purlins provides restraints to purlins laterally and rotationally. The restraints to purlins may reduce the critical load or increase the strength of the sections. In this study the effect of lateral and rotational restraints needs to be investigated taking into consideration local, distortional, and lateral torsional buckling for detached and connected purlins as well as changing of geometry of the members. Achieving this requires determining of appropriate lateral linear spring of stiffness K and rotational spring stiffness CD (British standard Institution, 2009). Buckling is considered critical phenomena in various cold formed cross-sections for majority of load cases before achieving yield point. The results obtained from Theoretical equations will be compared with those obtained from finite element analysis using ANSYS (release 12) for various dimensions of the purlins. The boundary conditions, which are used for the finite element members, need special consideration depending on the shell type, for instance, shell 43. The purlins have been analysed using theoretical equations and ANSYS to predict the values of pure bending stresses and the combination of bending and warping torsion stresses as well as displacements